Groundwater travel time in the freshwater lenses of Samborombón Bay, Argentina - Carol, Eleonora Silvina (2010)
The Samborombón Bay area (Argentina) is a coastal plain environment that contains groundwater resources with high salinity. In addition, there are local freshwater lenses associated with shell ridges and sand sheets in the region. In this work, the groundwater travel time in these freshwater lenses is estimated based on their geological conditions, which include hydraulic conductivity, recharge, morphology and discharge to surface freshwater or to saline groundwater. Groundwater travel times in the freshwater lenses were calculated from the equations developed by Chesnaux andAllen. The travel times estimated for the different scenarios were relatively short. The results indicate that the groundwater flow tends to be strongly dependent on the recharge conditions, with an excess of water in the water balance. The results can be applied to help design sustainable management methods to exploit this water resource system and also to assess the impact of contaminant plumes on this groundwater resource.